The effect of time-of-day on short-term repetitive maximal performance, cognitive ability and psychological variables in adolescents - Rawdha Hasni; Ibrahim Ouergui; Achraf Ammar; Khaled Trabelsi; Luca Paolo Ardigò; Hamdi Chtourou (PLoS ONE, 2025)
Previous studies investigating the diurnal variation of physiological and psychological variables during exercise have yielded conflicting results. The present investigation was designed to assess the impact of time-of-day on short-term repetitive maximal performance [i.e., single and two consecutive bouts of 5m shuttle run test (5mSRT), long jump test] as well as cognitive ability and psychological variables [i.e., mood states (POMS) and Hooper questionnaire] in male and female adolescents. In a randomized study design, 21 healthy adolescents (12 females and 9 males; age: 15.9±1.04 years) performed at 08h00 and 16h00 two consecutive 5mSRT (with 20 min of rest interval in-between), to assess the greatest distance (GD), the total distance (TD), the average distance (AD) and the fatigue index (FI), and the long jump test (LJT). Perceived exertion (RPE) was recorded immediately after each 5mSRT. The POMS and Hooper questionnaires and the digit-cancellation test (i.e., attention) were realized during each session. The results showed that TD and AD were greater in the morning than in the afternoon during the 1st (p = 0.048 and 0.048, respectively) and the 2nd (p = 0.0016 and 0.0017, respectively) 5mSRT; while GD was time-of-day independent (p = 0.16). For the FI, results demonstrated a significant time-of-day effect with highest values recorded in the afternoon compared to the morning during the 2nd 5mSRT (p = 0.017). In contrast, attention scores and the long jump test performance recorded before and after each 5mSRT were time-of-day independent for all measures (p > 0.05). Likewise, POMS parameters [anxiety (p = 0.15), depression (p = 0.71), anger (p = 0.23), fatigue (p = 0.07), confusion (p = 0.58), vigor (p = 0.16), TMD (p = 0.06) and interpersonal relationships (p = 0.19)], RPE [1st (p = 0.22) and 2nd (p = 0.43) 5mSRT] and delayed onset muscle soreness (p = 0.34) were time-of-day independent; while, fatigue (p = 0.03), sleep (p = 0.01) and stress (p = 0.027) estimated by the Hooper questionnaire were higher in the afternoon compared to the morning. In conclusion, morning is more effective than afternoon session for improving short-term repetitive maximal performance and reducing fatigue during the 5mSRT for adolescents. However, regarding psychological parameters and cognitive function and contrarily to previous researches, there is no time-of-day effects.